2011
DOI: 10.1103/physrevc.84.034607
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic approximation versus exact Faddeev method for (d,p) and (p,d) reactions

Abstract: The finite range adiabatic wave approximation provides a practical method to analyze (d,p) ≈ 5% for a range of beam energies (E d ≈ 20 − 40 MeV) but differences increase significantly for very low energies and for the highest energies. Our tests show that ADWA agrees best with Faddeev when the angular momentum transfer is small ∆l = 0 and when the neutron-nucleus system is loosely bound.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
93
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 38 publications
(61 reference statements)
10
93
0
1
Order By: Relevance
“…There is an understanding that DWBA does not provide an accurate description of this reaction (e.g., [38]) and that an effective deuteron optical potential that does not explicitly account for np breakup is unreliable [2]. The strong variation of the minimum found between the uncorrelated and correlated cases can be a symptom of the reaction model simplification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an understanding that DWBA does not provide an accurate description of this reaction (e.g., [38]) and that an effective deuteron optical potential that does not explicitly account for np breakup is unreliable [2]. The strong variation of the minimum found between the uncorrelated and correlated cases can be a symptom of the reaction model simplification.…”
Section: Discussionmentioning
confidence: 99%
“…However, these investigations typically rely on the comparison of two models or parameterizations. Concerning (a), for example, methods such as the adiabatic approximation or continuum-discretized coupled channels method have been benchmarked against the Faddeev method [2][3][4]. To address (b), the uncertainty from the effective interactions used, the standard procedure is to use two different parameterizations of the optical model within the same reaction theory framework, with the percent errors coming from the difference between the results obtained with these two parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Lotay et al [9,10] identified [23]. This three-body method incorporates deuteron breakup and has been proven to provide a good description of the transfer process when compared to exact solutions of the three-body problem [24]. For the nucleontarget optical potentials we use CH89 [25] and for the NN interaction ref.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, much work has gone into establishing the methods used to solve the three-body scattering problem. Examples are the benchmarks of the adiabatic wave approximation method and the continuum discretized coupled-channel method against the exact Faddeev approach for transfer reactions [4,5]. In those studies, the system was treated as n + p + A, and no excitation was allowed for A.…”
Section: Core Excitation In (Dp) Reactionsmentioning
confidence: 99%
“…In Fig.2 the symbols show the results obtained for the three-body binding energy of 6 Li for a variety of NN interactions commonly used in our field, as a function of their prediction for the probability of the deuteron d-state. Note that only the NN interaction is varied, the 4 He-N system is kept fixed with the parameters described in Ref. [10].…”
Section: Toward a Faddeev Theory For (Dp) On Heavy Nucleimentioning
confidence: 99%